"Cation/anion with co-solvation" type high-voltage aqueous electrolyte enabled by strong hydrogen bonding. (August 2022) - Hou, Ruilin; Wang, Yue; Sun, Yinglun; Lang, Junwei; Yang, Shengrong; Yan, Xingbin
Abstract: Aqueous electrolytes are important charge transport media in various electrochemical applications. However, the water splitting seriously limits the operation voltage of aqueous electrolytes. Thus, further widening the electrochemical stability window (ESW) of aqueous electrolytes is great of importance. Here, based on the high charge density and high electro-negativity of halogen anions (F - ), we proposed a "cation/anion with co-solvation" type 16 m KF aqueous electrolyte that can achieve a high conductivity of 196 mS cm −1, a record 3.4 V ESW based on stainless steel mesh and even 6.72 V ESW based on Al metal electrode that is much higher than the highest value currently reported. Such excellent feature is attributed to the strong hydrogen bonds between the F - anions and the water molecules at high concentrations. This work is helpful to provide a new path for design of ideal high-voltage aqueous electrolytes and to understand the important role of anions in aqueous electrolytes at the molecular level. Graphical Abstract: A new "cation/anion with co-solvation" type 16 m KF aqueous electrolyte with a record high ESW of 6.72 V has been developed, which could be attributed to its unique bulk/interface structure constructed by the strong hydrogen bonds between anion and water. ga1 Highlights: Developed a new "cation/anion with co-solvation" type 16 m KF aqueous electrolyte. The electrolyte has record voltage window of 6.72 V based on Al. The electrolyte has high conductivity of 196 mS cm −1 . Pointed out the important role of the strong hydrogen bonds. Revealed the unique transformation of the bulk/interface structure.